The effectivity of thidiazuron and 1‐naphthaleneacetic acid on somatic embryo induction in transgenic Dendrobium phalaenopsis Fitzg. carrying 35S::GR::AtRKD4 - Muhammad Ilham; Fitriana Puspitasari; Endang Semiarti (Universitas Gadjah Mada, 2022)
Dendrobium phalaenopsis Fitzg. (also known as the Larat orchid) is an endemic orchid from Larat Island, Eastern Indonesia. Its beautiful flowers mean that many plants are taken for commercial purposes, leading to the rapid decline of populations in their natural habitats. The objectives of this study were to determine which organs of the transgenic Larat orchid carrying the 35S::GR::AtRKD4 construct, together with which concentrations of the plant growth regulators (PGRs) auxin and cytokinin, are suitable for the induction of somatic embryos (SEs). In this study, the AtRKD4 gene in Larat orchids was confirmed using PCR with specific primers for the AtRKD4 and HPT genes. Thidiazuron (TDZ) (1, 3 and 5 mg/L) in combination with 1‐naphthaleneacetic acid (NAA) (0.5 and 1 mg/L) were used on new phalaenopsis (NP) medium to induce SEs from leaves, pseudobulbs and roots. The AtRKD4 transgenes were detected as being stably integrated into the DNA genome of transformant plants using specific primers for AtRKD4 and HPT genes, and positive results were obtained using actin gene primers as internal controls for PCR. Pseudobulbs produced 19 to 20 SEs from 108 pseudobulb explants (89–100%), a higher number than produced in explants of the other organs studied. Among the PGR treatments, the best results were obtained in NP medium supplemented with a combination of 1 mg/L TDZ and 1 mg/L NAA, 100% of the explants of which produced SEs (2.11 ± 1.36). No significant difference was found between the morphology of the SEs produced from the non‐transformant Larat orchid pseudobulb explants and the 35S::AtRKD4 carrier transformant.